Evaluation of equine assisted learning in education for primary school children: a qualitative study of the perspectives of teachers - Stoppard, Lorna; Donaldson, Jayne (Frontiers in Education, 2024)
The study presents qualitative research on the impact of Equine Assisted Learning in Education (EALE) has on the development of life skills in children as perceived by teachers and programme trainer. A qualitative design was utilised with semi structured interviews of the 8 participants investigating what changes were observed in the children’s cognitive, psychomotor and social skills were during and or after participation in the EALE. Data was analysed using thematic analysis. Four themes emerged, including, (i) relationships and trust, (ii) communication and confidence, (iii) achievement, (iv) teamwork and participation. The study identified cognitive, social and psychomotor learning for children across the four themes. This study found that there was increased interaction with each other, increased nonverbal communication and group work which was transferred into the classroom after the EALE and was reported to be seen for a considerable time after the programme ended. This supports previous research investigating the impact of EALE in children and supports its use as an alternative to classroom teaching for those who struggle to engage in the conventional classroom.